CIPP Evaluation Model (Context, Input, Process, Product) Program For Strengthening Character Education Through Thematic Learning In The Era Of The Covid-19 Pandemic - Siti Paridah; Otib Satibi Hidayat; Gantina Komalasari (Buana Pendidikan, 2022)
The background of this research is that the CIPP evaluation model (Context, Input, Process, Product) is one of the comprehensive evaluation models carried out in the world of education, and the phenomenon of bullying in elementary schools reinforces the need for strengthening character education, especially now that the covid-19 pandemic is strengthening. Character education is needed, one of which is through thematic learning. The method used in this research is a literature review study. This study uses the critical appraisal method to determine the success of the CIPP evaluation model in the PPK program through thematic learning in the covid-19 pandemic era and to determine the effectiveness of thematic learning in the PPK program in the covid-19 pandemic era.The results of the study show that 1) in maintaining the success of the CIPP evaluation model in the PPK program through thematic learning of the covid-19 pandemic era, a comprehensive evaluation is carried out consisting of; evaluation of the context covering the basis of policies, perceptions of needs and objectives of character education programs, evaluation of inputs which include planning, strategy, organizational structure design, implementation procedures and availability of character education program resources; process evaluation which includes coordination, implementation and supervision of the implementation of character education programs; and product evaluation which includes the achievement and impact of character education programs, 2) in the effectiveness of thematic learning in the covid-19 pandemic era PPK program, namely the implementation of online learning containing character education in the covid-19 season including; course design (course design); learner motivation; time management (time management); and convenience with online technologies (comfortabeness with online technologies).